Graphite composite material and preparation method thereof, negative electrode active material, secondary battery and electrical equipment

By coating the surface of the graphite material with nitrogen-doped porous alumina-carbon composite, the problem of inefficiency of graphite negative electrode materials in lithium-ion batteries during the first charge and discharge process is solved, and the effect of improving the battery energy density and rate performance is achieved.

CN116722122BActive Publication Date: 2025-03-07SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310783638.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-03-07
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

In lithium-ion batteries, the graphite negative electrode material will form an SEI film during the first charging and discharging process, resulting in low lithium ion consumption and efficiency, limiting the increase in battery energy density.

Method used

By coating the surface of the graphite material with nitrogen-doped porous alumina-carbon composite, the first-time efficiency of the graphite material is improved by using porous alumina without consuming lithium ions and forming an SEI film.

Benefits of technology

The first efficiency of graphite materials is improved, the rate performance of the battery is improved, and the liquid absorption and liquid retention capacity of the material and the ion transmission efficiency are improved through the porous structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116722122B_ABST
    Figure CN116722122B_ABST
Patent Text Reader

Abstract

The present invention discloses a graphite composite material and a preparation method thereof, a negative electrode active material, a secondary battery and an electric device. The graphite composite material comprises a core and a coating layer located on the surface of the core; wherein the material of the core comprises graphite, and the material of the coating layer comprises a nitrogen-doped porous aluminum oxide-carbon composite material. The graphite composite material provided by the present invention improves the first efficiency of the graphite material and improves the rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a graphite composite material and a preparation method thereof, a negative electrode active material, a secondary battery and electrical equipment. Background Art

[0002] Graphite has become a commonly used carbon negative electrode material in lithium-ion batteries due to its good conductivity, high crystallinity, and good layered structure. However, during the initial charge and discharge process of lithium-ion batteries, a certain amount of active lithium ions will be consumed due to the formation of a SEI film interface on the graphite negative electrode side, resulting in a low initial efficiency of the graphite negative electrode, which restricts the further improvement of the energy density of lithium-ion batteries.

[0003] Therefore, how to improve the initial efficiency of graphite materials to further increase the energy density of batteries has become an urgent problem to be solved. Summary of the invention

[0004] The invention provides a graphite composite material, which can improve the initial efficiency of the graphite material and the rate performance of the battery.

[0005] In a first aspect, the present invention provides a graphite composite material, comprising a core and a coating layer located on the surface of the core; wherein the material of the core comprises graphite, and the material of the coating layer comprises a nitrogen-doped porous alumina-carbon composite material.

[0006] Furthermore, in the graphite composite material, the mass proportion of the coating layer is 2 to 10 wt%.

[0007] Furthermore, the graphite includes at least one of spherical natural graphite, flake graphite, and artificial graphite.

[0008] Furthermore, the material of the coating layer is doped with non-metal atoms, and the non-metal atoms include at least one of sulfur and phosphorus.

[0009] In a second aspect, the present invention provides a method for preparing a graphite composite material, comprising the following steps:

[0010] Dispersing graphite and aluminum carboxylate in a first organic solvent to obtain solution A;

[0011] dispersing a basic coupling agent in a second organic solvent to obtain a solution B;

[0012] The solution A, the solution B, the oxidant and the nitrogen source are mixed, and then subjected to a solvothermal reaction to obtain an intermediate;

[0013] The intermediate is sintered under a protective atmosphere to obtain the graphite composite material.

[0014] Furthermore, the graphite includes at least one of spherical natural graphite, flake graphite, and artificial graphite.

[0015] Furthermore, the aluminum carboxylate salt includes at least one of aluminum citrate, aluminum stearate, dihydroxyamino aluminum acetate, aluminum acetate, aluminum acrylate, and aluminum oleate.

[0016] Furthermore, the first organic solvent includes polyethylene glycol.

[0017] Furthermore, the mass ratio of the aluminum carboxylate salt to the graphite is 5 to 15:100.

[0018] Furthermore, the mass percentage of the aluminum carboxylate salt and the first organic solvent is 0.5 wt % to 5 wt %.

[0019] Furthermore, the alkaline coupling agent includes an aluminum-based coupling agent containing an amino functional group.

[0020] Furthermore, the alkaline coupling agent includes at least one of 5-aminoaluminum-3-carboxylic acid methyl ester, diisopropyldithiocarbamate aluminum, and dihydroxyaminoaluminum acetate.

[0021] Furthermore, the second organic solvent includes at least one of cyclohexane, xylene and acetone.

[0022] Furthermore, the mass percentage of the alkaline coupling agent and the second organic solvent is 1 wt % to 10 wt %.

[0023] Furthermore, the oxidant includes hydrogen peroxide.

[0024] Furthermore, the nitrogen source includes at least one of urea, melamine, pyrrole and aniline.

[0025] Furthermore, the mass ratio of the solution A, the solution B, the oxidant and the nitrogen source is 500:50-150:1-10:1-10.

[0026] Furthermore, the solvent thermal reaction is carried out at a pressure of 1 to 5 MPa.

[0027] Furthermore, the temperature of the solvent thermal reaction is 50 to 150° C., and the time of the solvent thermal reaction is 30 to 300 minutes.

[0028] Furthermore, the protective atmosphere includes at least one of nitrogen and an inert gas.

[0029] Furthermore, the heating rate of the sintering process is 1-10°C / min.

[0030] Furthermore, the sintering temperature is 600-1200° C., and the sintering time is 1-6 hours.

[0031] Furthermore, gas is introduced during the sintering process, and the gas includes at least one of hydrogen sulfide, phosphine, ammonia, sulfur dioxide, and nitrogen dioxide.

[0032] Furthermore, the volume ratio of the gas to the protective atmosphere is 1 to 5:10.

[0033] In a third aspect, the present invention provides a negative electrode active material, comprising the aforementioned graphite composite material; or, the negative electrode active material comprises the graphite composite material prepared by the aforementioned preparation method.

[0034] In a fourth aspect, the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises the aforementioned negative electrode active material.

[0035] In a fifth aspect, the present invention provides an electrical device comprising the aforementioned secondary battery.

[0036] Through one or more of the above embodiments of the present invention, at least the following technical effects can be achieved:

[0037] 1. In the graphite composite material provided by the present invention, the surface of the graphite material is coated with a nitrogen-doped porous alumina-carbon composite material, which relies on the porous alumina not consuming lithium ions and not forming a SEI film during the charge and discharge process, thereby improving the initial efficiency of the graphite material.

[0038] 2. In the graphite composite material provided by the present invention, the coating layer material is doped with nitrogen, which gives the coating layer material more active sites, thereby improving the electronic conductivity of the graphite material and improving the rate performance of the battery.

[0039] 3. In the graphite composite material provided by the present invention, the coating layer material has a porous structure, which makes the graphite material have a high specific surface area, improves the material's ability to absorb and retain liquid, and is beneficial to the transmission of ions.

[0040] 4. In the preparation method of the graphite composite material provided by the present invention, organic aluminum salt is used as the aluminum source, which has milder reaction conditions than inorganic aluminum salt, and has good coating uniformity. In addition, the organic aluminum salt forms a porous structure after carbonization, which is beneficial to improving the dynamic performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The technical solutions and other beneficial effects of the present invention will be made apparent by describing in detail the specific embodiments of the present invention in conjunction with the accompanying drawings.

[0042] Figure 1This is a scanning electron microscope (SEM) image of the graphite composite material provided by the present invention. DETAILED DESCRIPTION

[0043] The technical scheme in the embodiment of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0044] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the term "and / or" herein is merely a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " herein, unless otherwise specified, generally indicates that the associated objects before and after are in an "or" relationship.

[0045] As described in the background technology, when graphite is used as the negative electrode material of lithium-ion batteries, a SEI film will be formed on the graphite surface during the first charge and discharge, which consumes some lithium ions, resulting in low initial efficiency of the battery, which restricts further improvement of the energy density of lithium-ion batteries.

[0046] In order to solve this technical problem, the present invention provides a graphite composite material with high efficiency and rate performance by coating the graphite material. The structure and preparation method of the graphite composite material are described in detail below.

[0047] The graphite composite material provided by the present invention has a core-shell structure, comprising a core and a coating layer coated on the surface of the core, wherein the material of the core comprises graphite, and the material of the coating layer comprises a nitrogen-doped porous alumina-carbon composite material.

[0048] In the present invention, there is no restriction on the type of graphite in the core, for example, it can be at least one of spherical natural graphite, flake graphite, and artificial graphite. Preferably, the graphite is artificial graphite. There is no particular restriction on the particle size of the graphite in the present invention. Generally, the D50 particle size of the graphite can be controlled between 1 and 50 μm.

[0049] In the present invention, the graphite can be either unmodified graphite or modified graphite, and the present invention does not limit this. The modified graphite can be, for example, graphite doped with silicon material, graphite doped with conductive carbon material, and the like.

[0050] In the present invention, the aluminum oxide-carbon composite material in the coating layer presents a porous structure. The presence of these pores improves the wettability of the electrolyte to the graphite material and the liquid storage and retention capacity of the graphite material.

[0051] In the present invention, a certain amount of nitrogen atoms are doped in the coating material. The presence of nitrogen atoms gives the coating material more active sites, and the presence of more active sites is conducive to the transmission of electrons, so the doping of nitrogen atoms improves the electronic conductivity of the graphite material.

[0052] In the graphite composite material of the present invention, the mass proportion of the coating layer needs to be controlled within a certain range. If the mass proportion is too low, the complete coating of the graphite particles cannot be achieved; if the mass proportion is too high, the proportion of active substances in the graphite composite material will be low, affecting the energy density of the battery. Generally, the mass proportion of the coating layer can be controlled to be 2 to 10wt%, for example, it can be any value among 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, or a range consisting of any two values ​​therein.

[0053] In some embodiments of the present invention, the coating layer material is further doped with non-metal atoms, including but not limited to at least one of sulfur and phosphorus. The doped non-metal atoms can also play a role in increasing the activity of the material, further improving the electronic conductivity of the graphite material.

[0054] The graphite composite material provided by the present invention has the following advantages:

[0055] (1) Since aluminum oxide is relatively inert to lithium ions and will not react with the electrolyte to form a film layer containing SEI components such as lithium carbonate, coating the surface of the graphite material with an aluminum oxide layer can reduce the consumption of lithium ions caused by the formation of the SEI film during the charge and discharge process of the graphite negative electrode, thereby improving the initial efficiency of the graphite.

[0056] (2) Nitrogen atoms doped in the coating material can enhance the electronic conductivity of the material and reduce impedance, thereby improving the rate performance of the battery.

[0057] (3) The carbon material in the coating layer is obtained by carbonizing an organic compound. It is an amorphous carbon with a porous structure, which is not only conducive to the transmission of ions but also can improve the electronic conductivity of the graphite material.

[0058] (4) The porous structure can increase the specific surface area of ​​the material, which is beneficial to improving the wettability of the electrolyte to the graphite material and improving the liquid absorption and retention capacity of the graphite material; at the same time, the porous structure is conducive to the transmission of ions and is beneficial to improving the kinetic performance of the battery.

[0059] The present invention further provides a method for preparing the above graphite composite material, comprising the following steps:

[0060] S1. dispersing graphite and aluminum carboxylate in a first organic solvent to obtain a solution A;

[0061] S2. dispersing the basic coupling agent in a second organic solvent to obtain a solution B;

[0062] S3. After mixing the solution A, the solution B, the oxidant and the nitrogen source, a solvothermal reaction is performed to obtain an intermediate;

[0063] S4. Sintering the intermediate under a protective atmosphere to obtain the graphite composite material.

[0064] In the above step S1, the graphite can be at least one of spherical natural graphite, flake graphite, and artificial graphite. Preferably, the graphite material is artificial graphite.

[0065] In the subsequent preparation process, the aluminum carboxylate salt will form a porous structure of aluminum oxide coated on the surface of graphite. The present invention selects the aluminum carboxylate salt as an organic aluminum salt. Compared with inorganic aluminum salts, the reaction conditions of organic aluminum carboxylates are milder. In the subsequent solvent thermal reaction, an aluminum oxide precursor can be formed to coat the surface of graphite particles, and the coating uniformity is better; and the organic aluminum carboxylate salt will form a porous structure after carbonization, which is beneficial to improving the dynamic performance of the battery.

[0066] In the present invention, the aluminum carboxylate salt includes but is not limited to at least one of aluminum citrate, aluminum stearate, dihydroxyamino aluminum acetate, aluminum acetate, aluminum acrylate, and aluminum oleate.

[0067] In the present invention, the mass ratio of aluminum carboxylate to graphite is preferably 5 to 15:100, for example, it can be any value of 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, 15:100 or a range consisting of any two values ​​thereof. If the mass ratio of aluminum carboxylate is too low, a complete coating layer cannot be formed on the graphite surface; if the mass ratio of aluminum carboxylate is too high, the coating layer formed will be too thick, so that the proportion of active substances in the graphite composite material is too low, affecting the energy density of the battery.

[0068] In the present invention, the first organic solvent is mainly used to dissolve the aluminum carboxylate and disperse the graphite. The first organic solvent is preferably a solvent that is difficult to volatilize, so that the first organic solvent will not volatilize during the subsequent drying and calcining process, but will carbonize to form a porous carbon material during the calcining process to improve the conductivity of the graphite composite material. In a preferred embodiment, the first organic solvent is polyethylene glycol (PEG), which has good mutual solubility with other organic solvents and is not easy to volatilize.

[0069] In the present invention, the mass percentage of the aluminum carboxylate salt and the first organic solvent is preferably 0.5wt% to 5wt%, for example, it can be any value among 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% or a range consisting of any two values ​​therein.

[0070] In the present invention, when preparing solution A, the order of adding graphite and aluminum carboxylate salt is not limited, for example, the aluminum carboxylate salt can be first dissolved in the first organic solvent, and then graphite is added and dispersed evenly. Alternatively, graphite is first added and dispersed evenly, and then aluminum carboxylate salt is added.

[0071] In step S2 of the present invention, the alkaline coupling agent has the function of improving the dispersibility of graphite in the solvent, thereby improving the uniformity of coating in the subsequent preparation process; and the function of the alkaline coupling agent is to react with the aluminum carboxylate salt to obtain an aluminum oxide precursor.

[0072] The above-mentioned alkaline coupling agent is preferably an aluminum-based coupling agent, and is further preferably an aluminum-based coupling agent containing an amino group. The amino group in the aluminum-based coupling agent containing an amino group will be doped into the coating layer in the form of a nitrogen atom during the subsequent preparation process, which is beneficial to improve the electronic conductivity of the graphite composite material. In some embodiments, the alkaline coupling agent includes but is not limited to at least one of 5-aminoaluminum-3-carboxylate, diisopropyldithiocarbamate, and dihydroxyaminoaluminum acetate.

[0073] In the present invention, the second organic solvent needs to be able to dissolve the alkaline coupling agent and have good miscibility with the first organic solvent. The second organic solvent that meets the requirements includes but is not limited to at least one of cyclohexane, xylene, and acetone.

[0074] In the present invention, the mass percentage of the basic coupling agent and the second organic solvent is preferably 1wt% to 10wt%, for example, it can be any value among 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or a range consisting of any two values ​​therein.

[0075] It should be pointed out that the present invention separates the aluminum carboxylate salt and the alkaline coupling agent into solution A and solution B respectively. The reason is that these two components are acidic and alkaline respectively. If they are mixed together to form a solution, an acid-base reaction will occur. Therefore, they need to be dissolved separately to form a solution, which is also conducive to uniform dispersion of graphite.

[0076] In step S3 of the present invention, after solution A, solution B, oxidant and nitrogen source are evenly mixed, an aluminum oxide precursor is formed through a solvent thermal reaction and coated on the surface of the graphite particles; at the same time, the nitrogen source forms nitrogen free radicals in the reaction and is doped into the aluminum oxide precursor; and the presence of the nitrogen source can increase the pore structure inside the coating layer, which is beneficial to improving the specific surface area and liquid absorption capacity of the material.

[0077] The role of the above-mentioned oxidant is to catalyze the acid-base reaction between the aluminum carboxylate salt and the alkaline coupling agent. The oxidant can be selected from oxidants commonly used in the art, preferably hydrogen peroxide. When hydrogen peroxide is used as an oxidant, it is reduced during the reaction process, and the obtained product is water, so no impurities are introduced into the system.

[0078] In the present invention, the nitrogen source can be selected from nitrogen-containing organic substances commonly used in the art, including but not limited to at least one of urea, melamine, pyrrole, and aniline.

[0079] In the present invention, the mass ratio of solution A, solution B, oxidant and nitrogen source is preferably 500:50-150:1-10:1-10. This ratio can ensure that a complete coating layer with appropriate thickness is formed on the surface of the graphite particles.

[0080] In the present invention, the solvent thermal reaction needs to be carried out in a high-pressure reaction vessel (such as a high-pressure reactor), and the reaction pressure is preferably 1-5 MPa, for example, it can be any value among 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa or a range consisting of any two values ​​therein.

[0081] Further, the temperature of the solvothermal reaction is 50-150°C, for example, any value among 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, or a range consisting of any two values ​​thereof. The time of the solvothermal reaction is 30-300 min, for example, any value among 30 min, 50 min, 80 min, 100 min, 120 min, 150 min, 180 min, 200 min, 220 min, 250 min, 270 min, 300 min, or a range consisting of any two values ​​thereof.

[0082] After the solvent thermal reaction is completed, the reaction product is collected and dried to obtain an intermediate. In some embodiments of the present invention, the product can be collected by filtering the reaction solution, centrifuging, etc. The collected product is then dried to remove the residual organic solvent (mainly the second organic solvent) for standby use. The drying method includes but is not limited to vacuum drying.

[0083] In step S4 of the present invention, the intermediate is subjected to a high-temperature sintering treatment. During the sintering process, the alumina precursor on the surface of the graphite particles forms porous alumina, and the organic matter in the intermediate (including the first organic solvent, the aluminum carboxylate salt and the organic matter in the alkaline coupling agent) is carbonized to form a carbon material, and finally the nitrogen-doped porous alumina-carbon composite material is coated on the graphite surface.

[0084] The sintering reaction is carried out in a sintering furnace (e.g., a tubular furnace) under a protective atmosphere. That is, the intermediate is transferred to a tubular furnace, a protective gas is introduced into the tubular furnace to exhaust the air in the tube, and then the temperature is raised to carry out the sintering reaction. During the sintering process, a protective gas is continuously introduced into the tube. The protective gas includes one or more of nitrogen and an inert gas, preferably argon.

[0085] In the present invention, the heating rate of the tubular furnace is 1 to 10°C / min, for example, it can be any value of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or a range consisting of any two values ​​thereof.

[0086] In the present invention, the temperature of the sintering reaction is 600-1200°C, for example, it can be any value of 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C or a range consisting of any two values ​​thereof.

[0087] In the present invention, the sintering reaction time is 1 to 6 hours, for example, it can be any value among 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, or a range consisting of any two values ​​thereof.

[0088] In a preferred embodiment, gas may be introduced during the sintering process, and the gas includes but is not limited to at least one of hydrogen sulfide, phosphine, ammonia, sulfur dioxide, and nitrogen dioxide. During the sintering process, non-metallic atoms (N, S, P) in the gas may also be doped into the coating layer, which may further improve the electronic conductivity of the material and reduce the impedance; at the same time, the introduced gas may easily form a pore structure on the surface of the material, thereby increasing the specific surface area of ​​the material.

[0089] In the present invention, the gas can be mixed with the protective gas and introduced into the tubular furnace together. In the mixed gas, the volume ratio of the gas is preferably 1 to 5:10, for example, it can be any value among 1:10, 2:10, 3:10, 4:10, 5:10 or a range consisting of any two values ​​thereof.

[0090] The present invention also provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is configured to separate the positive electrode sheet from the negative electrode sheet, wherein the negative electrode active material of the negative electrode sheet at least comprises the aforementioned graphite composite material.

[0091] The present invention also provides an electrical device, which includes the above-mentioned secondary battery and uses the secondary battery as a power supply for the electrical device. In some embodiments, the electrical device of the present invention includes but is not limited to: a backup power supply, a motor, an electric car, an electric motorcycle, a power-assisted bicycle, a bicycle, an electric tool, a large household battery, etc.

[0092] The present application is further described below in conjunction with the following examples and comparative examples. The following examples and comparative examples are not to be construed as limiting the technical solutions of the present application.

[0093] Example 1

[0094] S1. 10 g of aluminum citrate was added to 1000 g of polyethylene glycol to prepare a 1 wt % uniform solution, and then 100 g of artificial graphite was added and dispersed evenly to obtain a solution A;

[0095] S2. 5 g of 5-aminoaluminum-3-carboxylate was added to 100 g of cyclohexane organic solvent and dispersed evenly to obtain a 5 wt % solution B;

[0096] S3. Take 500g of solution A and 100g of solution B, add them to an autoclave, add 5g of hydrogen peroxide (concentration 30%), 5g of melamine, disperse them evenly, and react them at a temperature of 100°C and a pressure of 3Mpa for 90min, filter, and dry them in vacuum at 80°C for 24h to obtain an intermediate;

[0097] S4. The intermediate is transferred to a tube furnace, and argon gas is first introduced to exhaust the air in the tube, and then mixed gas (ammonia and argon, V 氨气 :V 氩气 =3:10, flow rate is 100 ml / min), the temperature is increased to 800°C at a heating rate of 5°C / min, and sintered for 3h to obtain a graphite composite material.

[0098] Example 2

[0099] S1. 5 g of aluminum stearate was added to 1000 g of polyethylene glycol to prepare a 0.5 wt % uniform solution, and then 100 g of artificial graphite was added and dispersed evenly to obtain a solution A;

[0100] S2. 1 g of aluminum diisopropyldithiocarbamate was added to 100 g of xylene organic solvent and dispersed evenly to obtain a 1 wt % solution B;

[0101] S3. Take 500g of solution A and 50g of solution B, add them to an autoclave, add 1g of hydrogen peroxide (concentration 30%), 1g of pyrrole, disperse them evenly, and react at a temperature of 50°C and a pressure of 5Mpa for 300min, filter, and dry in vacuo at 80°C for 24h to obtain an intermediate;

[0102] S4. The intermediate is transferred to a tube furnace, and argon is first introduced to exhaust the air in the tube, and then the mixed gas (phosphine and argon, V 磷化氢 :V 氩气 =1:10, flow rate is 100 ml / min), the temperature is increased to 600°C at a heating rate of 1°C / min, and sintered for 6h to obtain a graphite composite material.

[0103] Example 3

[0104] S1. 15 g of aluminum acetate was added to 1000 g of polyethylene glycol to prepare a 0.15 wt % uniform solution, and then 100 g of artificial graphite was added and dispersed evenly to obtain a solution A;

[0105] S2. 10 g of dihydroxyaluminum aminoacetate was added to 100 g of acetone organic solvent and dispersed evenly to obtain a 10 wt % solution B;

[0106] S3. Take 500g of solution A and 150g of solution B, add them to an autoclave, add 10g of hydrogen peroxide (concentration 30%) and 10g of urea, disperse them evenly, and react them at a temperature of 150°C and a pressure of 1Mpa for 30min, filter, and dry them in vacuum at 80°C for 24h to obtain an intermediate;

[0107] S4. The intermediate is transferred to a tube furnace, and argon is first introduced to exhaust the air in the tube, and then the mixed gas (sulfur dioxide and argon, V 二氧化硫 :V 氩气 =5:10, flow rate of 100 ml / min), heating to 1200°C at a heating rate of 10°C / min, sintering for 1 h to obtain a graphite composite material.

[0108] Comparative Example 1

[0109] S1. 100 g of aluminum chloride was added to 500 g of deionized water, followed by 3 g of 5-aminoaluminum-3-carboxylic acid methyl ester and 1000 g of artificial graphite, and the mixture was mixed evenly; 30 g of aqueous ammonia was then added, and the mixture was transferred to a high-pressure reactor, reacted at a temperature of 100 ° C and a pressure of 3 MPa for 60 min, filtered, and dried under vacuum at 80 ° C for 24 h to obtain a precursor material;

[0110] S2. Transfer the precursor material to a tube furnace, first introduce argon gas to remove the air in the tube, and then introduce a mixed gas (consisting of ammonia and argon, V氨气 :V 氩气 =3:10, flow rate 10 ml / min), and heated to 800°C at a heating rate of 5°C / min, and sintered for 3h to obtain a graphite composite material.

[0111] Comparative Example 2

[0112] The difference between Comparative Example 2 and Example 1 is that in step S2, when preparing solution B, 5-aminoaluminum-3-carboxylic acid methyl ester is not added.

[0113] Comparative Example 3

[0114] The difference between Comparative Example 3 and Comparative Example 1 is that in step S4, during the sintering process, the gas introduced into the tubular furnace is pure argon gas, and no ammonia gas is introduced.

[0115] Comparative Example 4

[0116] The difference between Comparative Example 4 and Example 1 is that no melamine nitrogen source is added in step S3.

[0117] Performance Testing

[0118] 1. SEM test

[0119] The graphite composite material prepared in Example 1 was subjected to SEM test, and the test results are as follows: Figure 1 shown.

[0120] Depend on Figure 1 It can be seen that the graphite composite material prepared in Example 1 is in a granular form, has a small amount of porous structure on the surface, and has a particle size D50 between 8 and 15 μm.

[0121] 2. Physical and chemical properties and button battery test

[0122] 2.1 Physical and chemical properties test

[0123] According to the method specified in GBT-24533-2019 "Graphite Anode Materials for Lithium Ion Batteries", the powder OI value, specific surface area, and tap density of the graphite composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were tested. The test results are shown in Table 1.

[0124] 2.2 Button assembly

[0125] The graphite composite materials in Examples 1-3 and Comparative Examples 1-4 were used as negative electrode materials for lithium-ion batteries and assembled into button batteries. The specific preparation method of the negative electrode materials was as follows:

[0126] The graphite composite material, CMC, SBR, SP, and H2O were mixed in a mass ratio of 95:2.5:1.5:1:150 to prepare the negative electrode sheet. The lithium sheet was used as the positive electrode, and the electrolyte was LiPF6 / EC+DEC (LiPF6 was the electrolyte, a mixture of EC and DEC with a volume ratio of 1:1 was the solvent, and the electrolyte concentration was 1.3 mol / L); the diaphragm was a composite film of polyethylene PE, polypropylene PP, and polyethylene propylene PEP. The button cell was assembled in an argon-filled glove box.

[0127] 2.3 Power-off performance test

[0128] The electrochemical performance of the button cell was tested on a Wuhan Blue Electric CT2001A battery tester with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C. The first discharge capacity and first efficiency of the button cell, as well as the rate performance (2C / 0.1C) were tested. The test results are shown in Table 1.

[0129] Table 1 Physical and chemical properties of graphite composite materials and test results of electrical properties in the embodiments and comparative examples

[0130]

[0131]

[0132] Please refer to Table 1. In Example 1, since the graphite surface is coated with a porous alumina-carbon coating layer, the porous structure makes the specific surface area of ​​the graphite material larger, reaching 2.5m 2 / g; Due to the coating of alumina layer, the tap density of the material is improved to 1.19g / cm 3 ; And the OI value of the powder is low, only 2.4, which is conducive to ion diffusion and rate performance. In addition, the presence of the coating layer can improve the first efficiency and capacity of graphite and improve the rate performance of the battery. In this embodiment, the first discharge capacity of the buckle reached 361.2mAh / g, the first efficiency reached 96.2%, and the rate performance at 2C / 0.1C reached 92.1%.

[0133] Examples 2-3 showed similar results to Example 1. The first discharge capacity of the battery was above 359 mAh / g, the first efficiency was above 95.5%, and the rate performance at 2C / 0.1C was above 91%, showing excellent electrochemical performance.

[0134] In Comparative Example 1, the aluminum salt used is inorganic aluminum salt aluminum chloride. Aluminum chloride and ammonia water react under high temperature and high pressure to form aluminum hydroxide coated on the surface of graphite, and then sintered to obtain an aluminum oxide coating layer. The surface of the coating layer has no porous structure. Therefore, compared with Comparative Example 1, the specific surface area of ​​the graphite material has significantly decreased to 2.0 m 2 / g; and the powder OI value has increased significantly, reaching 3.7. In terms of electrochemical performance, the graphite composite material of Comparative Example 1 has no porous structure on the surface, which will affect the ability to absorb and retain liquid, reduce the rate performance of the battery, and also have a certain impact on the first efficiency and capacity of the battery. From the results, the first discharge capacity of the battery is 355.5mAh / g, the first efficiency is 94.4%, and the rate performance at 2C / 0.1C is only 87.6%.

[0135] During the preparation of graphite composite materials, coupling agents can improve the dispersibility of graphite, which is conducive to the formation of a more uniform coating layer. At the same time, the presence of nitrogen atoms in the coupling agent can improve the electronic conductivity of the material. In Comparative Example 2, no coupling agent was added to the graphite composite material during the preparation process, so a uniform coating layer could not be formed on the graphite surface, which resulted in a significant decrease in the first effect, capacity, and rate performance of the graphite composite material of Comparative Example 2. The first discharge capacity of the deduction was 352.3 mAh / g, the first efficiency was 92.2%, and the rate performance at 2C / 0.1C was only 84.7%.

[0136] Compared with Example 1, Comparative Example 3 did not introduce ammonia, which caused the electronic conductivity of the material shell to deteriorate, reducing the rate performance, and the rate performance at 2C / 0.1C was only 78.5%. Compared with Example 1, Comparative Example 4 did not add melamine nitrogen source, which caused the electronic conductivity of the material core to be poor, and the core had fewer pores, reducing its specific surface area, thereby reducing its rate performance, and the rate performance at 2C / 0.1C was only 85.3%.

[0137] 3. Soft pack battery test

[0138] 3.1 Preparation of soft pack batteries

[0139] The graphite composite materials in Examples 1-3 and Comparative Examples 1-4 were slurried and coated to prepare negative electrode sheets, NCM622 was used as the positive electrode, LiPF6 / EC+DEC+PC was used as the electrolyte (the solute was LiPF6, the concentration was 1.2 mol / L, and the solvent volume ratio EC:DEC:PC=1:1:1), and Celgard2400 membrane was used as the separator to prepare a 5Ah soft-pack battery.

[0140] 3.2 Electrochemical performance test

[0141] Liquid absorption capacity of the negative electrode: Use a 1mL burette and absorb V mL of electrolyte, add a drop on the surface of the above negative electrode, and time it until the electrolyte is completely absorbed. Record the time t and calculate the liquid absorption rate V / t of the electrode.

[0142] Cycle performance: charge and discharge current 1.0C / 1.0C, voltage range 2.8-4.2V, cycle number 500 times.

[0143] Rate performance: constant current ratio under 2C charging conditions, that is, constant current capacity / (constant current capacity + constant voltage capacity).

[0144] The above test results are shown in Table 2.

[0145] Table 2 Performance test results of soft pack batteries

[0146]

[0147] Please refer to Table 2. In Examples 1-3, since the coating layer on the surface of graphite has a porous structure, the specific surface area of ​​graphite is increased, so the negative electrode sheet shows a very high liquid absorption rate. At the same time, the soft-pack batteries of Examples 1-3 also have good cycle performance, and the cycle retention rate after 500 cycles is above 94.5%. In addition, since nitrogen doping is carried out by introducing ammonia during the sintering process, the active sites of the material are increased, the electronic conductivity of the material is improved, the impedance is reduced, and finally the constant current ratio of the graphite composite material is improved. Therefore, the 2C constant current ratio of the soft-pack batteries of Examples 1-3 is above 93.5%.

[0148] In Comparative Example 1, since the coating layer on the graphite surface has no porous structure, the liquid absorption rate of the negative electrode sheet is very low. The lower liquid absorption rate will also affect the cycle performance of the battery. The cycle retention rate of the soft-pack battery in Comparative Example 1 after 500 cycles is only 87.9%, and the 2C constant current ratio is only 89.3%.

[0149] In Comparative Example 2, since no coupling agent was added during the preparation of the graphite composite material, the dispersion of the graphite was affected, and the coating effect was eventually affected to a certain extent. From the results, compared with Examples 1-3, the cycle retention rate and 2C constant current ratio of the soft-pack battery in Comparative Example 2 have decreased to a certain extent, and the cycle retention rate after 500 cycles is only 89.3%, and the 2C constant current ratio is only 88.2%.

[0150] Comparative Example 3 did not introduce ammonia during the sintering process, and Comparative Example 4 did not add a nitrogen source during the solvent thermal reaction, which not only resulted in fewer pores on the surface and core of the material, affecting the specific surface area and liquid absorption rate of the material; but also caused the concentration of nitrogen doping in the coating layer to decrease, affecting the electronic conductivity of the material, increasing the battery impedance, and ultimately reducing the rate performance and cycle performance of the battery. From the results, the soft-pack batteries of Comparative Examples 3-4 had a cycle retention rate of less than 88% after 500 cycles, and a 2C constant current ratio of less than 87%, which was significantly reduced compared with Examples 1-3.

[0151] In summary, although the present invention has been disclosed as above in terms of preferred embodiments, the above preferred embodiments are not intended to limit the present invention. A person skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined in the claims.

Claims

1. A graphite composite material, characterized in that: It comprises a core and a coating layer located on the surface of the core; wherein the material of the core comprises graphite, and the material of the coating layer comprises a nitrogen-doped porous alumina-carbon composite material; The graphite composite material is prepared by the following graphite composite material preparation method, and the preparation method comprises the following steps: Dispersing graphite and aluminum carboxylate in a first organic solvent to obtain solution A; dispersing a basic coupling agent in a second organic solvent to obtain a solution B; The solution A, the solution B, the oxidant and the nitrogen source are mixed, and then subjected to a solvothermal reaction to obtain an intermediate; Sintering the intermediate under a protective atmosphere to obtain the graphite composite material; The basic coupling agent includes an aluminum-based coupling agent containing an amino functional group.

2. The graphite composite material according to claim 1, characterized in that In the graphite composite material, the mass percentage of the coating layer is 2-10wt%; and / or, The graphite includes at least one of spherical natural graphite, flake graphite, and artificial graphite; and / or, The material of the coating layer is also doped with non-metal atoms, and the non-metal atoms include at least one of sulfur and phosphorus.

3. A method for preparing a graphite composite material, characterized in that: The following steps are involved: Dispersing graphite and aluminum carboxylate in a first organic solvent to obtain solution A; dispersing a basic coupling agent in a second organic solvent to obtain a solution B; The solution A, the solution B, the oxidant and the nitrogen source are mixed, and then subjected to a solvothermal reaction to obtain an intermediate; Sintering the intermediate under a protective atmosphere to obtain the graphite composite material; The basic coupling agent includes an aluminum-based coupling agent containing an amino functional group.

4. The method for preparing the graphite composite material according to claim 3, characterized in that: The graphite includes at least one of spherical natural graphite, flake graphite, and artificial graphite; and / or, The aluminum carboxylate salt comprises at least one of aluminum citrate, aluminum stearate, dihydroxyamino aluminum acetate, aluminum acetate, aluminum acrylate, and aluminum oleate; and / or, The first organic solvent comprises polyethylene glycol; and / or, The mass ratio of the aluminum carboxylate salt to the graphite is 5 to 15:100; and / or, The mass percentage of the aluminum carboxylate salt and the first organic solvent is 0.5 wt % to 5 wt %.

5. The method for preparing the graphite composite material according to claim 3, characterized in that: The aluminum-based coupling agent containing an amino functional group includes at least one of 5-aminoaluminum-3-carboxylic acid methyl ester, aluminum diisopropyldithiocarbamate, and dihydroxyaminoaluminum acetate; and / or, The second organic solvent comprises at least one of cyclohexane, xylene and acetone; and / or, The mass percentage of the basic coupling agent and the second organic solvent is 1 wt % to 10 wt %.

6. The method for preparing the graphite composite material according to claim 3, characterized in that: The oxidant comprises hydrogen peroxide; and / or, The nitrogen source includes at least one of urea, melamine, pyrrole and aniline; and / or, The mass ratio of the solution A, the solution B, the oxidant and the nitrogen source is 500:50-150:1-10:1-10; and / or, The solvothermal reaction is carried out at a pressure of 1 to 5 MPa; and / or, The temperature of the solvent thermal reaction is 50 to 150° C., and the time of the solvent thermal reaction is 30 to 300 minutes.

7. The method for preparing the graphite composite material according to claim 3, characterized in that: The protective atmosphere comprises at least one of nitrogen and an inert gas; and / or, The heating rate of the sintering process is 1 to 10°C / min; and / or, The sintering temperature is 600-1200° C. and the sintering time is 1-6 hours; and / or, During the sintering process, a gas is introduced, wherein the gas includes at least one of hydrogen sulfide, phosphine, ammonia, sulfur dioxide, and nitrogen dioxide; The volume ratio of the gas to the protective atmosphere is 1 to 5:

10.

8. A negative electrode active material, characterized in that: The invention comprises the graphite composite material as claimed in claim 1 or 2; or comprises the graphite composite material prepared by the preparation method as claimed in any one of claims 3 to 7.

9. A secondary battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The negative electrode sheet includes the negative electrode active material as claimed in claim 8.

10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped hard carbon coated artificial graphite composite material

    CN113889596A

  • Fast-charging graphite composite material and preparation method thereof

    CN115974114A